Acidentes de trabalho com altura na construção civil, em Uberlândia-MG, de 2016 a 2018 e suas implicações na saúde do trabalhador - Lima, Marcos Alcides Pereira de (2021)
Occupational accidents are present in workers lives. However, in civil construction, there is a huge amount of work accidents due to the increase in demand in this market over time, as well as due to the essence of activities that involve risks and can contribute to accidents of the most varied types. This thesis will address more specifically the work accidents in civil construction involving exposure to heights in the city of Uberlândia, once the city, from 2016 to 2018 was in its full expansion and significantly demanded workforce in this sector. Among the thesis aims are the research about the contingent of accidents with falls, identifying them and knowing their effects on the health of workers working in the civil construction sector in the city and their implications on workers' health, from 2016 to 2018. Through this, it is expected to propose alternatives to transform this reality, using examples such as eSocial and the National Plan to Avoid Informality of Employed Workers - Plancite, which are protective policies that can indicate ways to address the problem of this study . The methodology adopted in this research was based on quantitative approach, using descriptive statistics to calculate the data, which were collected from the Notifiable Diseases Information System (SINAN), referring to serious work accidents involving falls with workers from civil construction, from 2016 to 2018. Based on the analysis of the collected data, this thesis found that the mason profession is the one with the highest number of accidents with falls within the civil construction industry, and also that the majority of falls occur with the use of scaffolding in services on roofs. Furthermore, it was possible to identify that the year of 2017 was the one with the highest incidence of injuries resulting from accidents with falls and that from 2016 to 2018 there is a prevalence of injuries with greater severity.